Effect of pitch petroleum oxidation on mesophase production - Barraza-Burgos, Juan-Manuel (CT&F - Ciencia, Tecnología y Futuro, 2012)
This study used two Colombian petroleum pitches (an asphalt and a precipitate) to determine their capacity as precursor of carbonaceous materials. In order to obtain the mesophase, pitches were oxidized at temperature of 350°C and oxidation times of 2; 3 and 5 hours. Oxidized pitches were fractioned with toluene using a ratio of 20 mL Toluene/g of oxidized bitumen. Insoluble material in Toluene (IT) and Tetrahydrofurane (ITHF) were carbonized with nitrogen at 400°C. For the identification of the mesophase, specimens were fabricated with the material obtained from carbonization. For the quantification of the mesophase, a microscope with polarized light filter was used. A total of 500 points were counted. The results showed that the asphalt treated with the longest oxidation time, contained higher concentration of mesophase. By contrast, the precipitate treated with the shortest oxidation time produced higher concentration of mesophase.